WYOBRAŻENIA O ZAŚWIATACH DEMONICZNYCH NA PRZYKŁADZIE BAJEK O OSZUKANYM DIABLE - Piotrowski, Robert (Przegląd Rusycystyczny, 2018)
In this article author tries to find archaic motives of the sacrifice for demonic creatures, may be old forest deities, associated with folktales with a type of T 1030 „Devil deceived when dividing the crops” (Folktales of Aarne-Thompson-Uther type 1030 „Crop Division between Man and Ogre”). That creatures are presented in Polish folktales as a devil, or as a bear depicted in Russian folktales. Cooperation between the host and the devil brings positive effects to the host, and the devil receives plants that are useless for human being.